Significance of zone 2 peak on capillary electrophoresis for the detection of haemoglobin constant spring - Hasan, Nik Fatma Fairuz Nik Mohd (2017)
Haemoglobin Constant Spring (Hb CS) is a point mutational defect of α thalassaemia at the termination codon and leads to α chain extension and reduced mRNA stability. It is a prevalent and common non deletional α thalassemia in most Southeast Asian countries. This abnormal haemoglobin has clinical heterogeneity and can interact with α° and cause non deletional Hb H CS. Screening for this abnormal haemoglobin is performed by capillary electrophoresis (CE). It is one of the analytical separation techniques and can be used to separate and quantitate Hb A2, Hb F and other abnormal haemoglobins. CE gives peak at the Zone 2 for Hb CS and it is a sensitive method to detect Hb CS. The aims of this study were to determine the significance of presence of Zone 2 peak on CE in diagnosing Hb CS, to compare the haematological profiles between different Hb CS genotypes and to estimate range for Zone 2 peak by CE with different Hb CS genotypes. A cross sectional study was done from July 2015 to July 2016 by collecting 137 samples randomly which showed positive peak on Zone 2 of CE. The samples were tested for red cell indices (Hb, RBC, MCV, MCH, and RDW) by using Sysmex XN 3000 analyzer, Sysmex Corporation, USA. Haemoglobin analyses were performed using CAPILLARYS2 Flex- Piercing System Sebia, PN 1227, France and DNA analyses using Multiplex PCR and ARMS were done for non deletional and deletional α thalassaemia.One hundred and eighteen (86.1%) out of 137 samples that showed positive peak in Zone 2 of CE, were positive for termination codon Hb CS mutation, confirmed by molecular analysis. The most common types of Hb CS found was Heterozygotes Hb CS which was 92 samples (67.2%), followed by compound heterozygotes which was 22 samples (16%) and homozygotes group which was 4 samples (2.9%). There were significant number of samples that had positive peak at Zone 2 which confirmed for termination codon CS mutation. The range of Hb CS level for Hb CS trait can be estimated to lie within mean of 0.67±0.27%. Meanwhile, the range of Hb CS level for compound heterozygotes Hb CS and homozygotes Hb CS were from 0.3 to 2.2 % and 4.5 to 5.5%, respectively. This might aid in making the diagnosis if the molecular technique is not available. Significant haematological differences which include Hb level, MCV, MCH, RDW, RBC count and Hb CS level were observed between heterozygotes, homozygotes and compound heterozygotes Hb CS. Consequently, we will able to predict these groups from the haematological indices and Hb CS level/ quantification on zone 2 peak if the molecular technology is not available.